Formic acid enabled selectivity boosting in transfer hydrogenation of 5-hydroxymethylfurfural to 2, 5-furandimethanol on highly dispersed Co–Nx sites. Issue 4 (23rd December 2020) - Xu, Ling; Nie, Renfeng; Chen, Xujie; Li, Yanchen; Jiang, Yuxi; Lu, Xiuyang
Abstract : Catalytic transfer hydrogenation (CTH) reaction is considered as a potential route for upgrading bio-based carbonyl compounds to their corresponding alcohols. Abstract : Catalytic transfer hydrogenation (CTH) reaction is considered as a potential route for upgrading bio-based carbonyl compounds to their corresponding alcohols. Herein, ordered mesoporous N-doped carbon confined Co–N x (Co–NC) was adopted as a catalyst for converting cellulose-derived 5-hydroxymethylfurfural (HMF) to 2, 5-furandimethanol (FDM) using formic acid (FA) as a hydrogen donor. Different catalysts and preparation methods were screened, by varying cobalt phases and template removal procedures. It is found that highly dispersed N-confined Co species (Co–N x ) other than naked Co NPs acted as catalytic species for the CTH of HMF with FA, which gave 86% yield of FDM at 100% HMF conversion. Kinetic experiments revealed that, compared with molecular hydrogen, Co–NC could effectively accelerate HMF hydrogenation and suppress as-formed FDM hydrogenolysis in the presence of FA, which is ascribed to its superior activity toward hydrogen transfer from FA and fast desorption toward FDM. Mechanism studies indicated that C–H dissociation of FA could be the rate-determining step in the CTH reaction, and the hydrogenation of HMF could proceed through an intermolecular hydride transfer route. This work shows that the bifunctional nature of the catalyst is critical in the efficient CTH of biomass-derived carbonyl compounds and provides insights toward the rational design of such catalysts.